Effectiveness Analysis of Village Fund Management in a Remote Papuan Village: Evidence from Bime - Aser Wisal; J Ary Mollet; Halomoan Hutajulu (Dynamics of Politics and Democracy, 2026)
Purpose: This study examines the effectiveness of village fund management in Bime Village, Bime District, Bintang Mountains Regency, Indonesia, and identifies the governance strategies adopted to sustain effective fund management in a remote highland setting. Research Methodology: A descriptive mixed-methods approach was employed by combining quantitative effectiveness ratio analysis with qualitative interviews. Secondary data on village fund revenue and expenditure realization from 2020–2024 were analyzed using the effectiveness ratio based on the Ministry of Home Affairs Decree No. 690.900.327 of 1996. Qualitative data were collected through interviews with village officials and members of the Village Consultative Body to explore governance strategies. Results: Village fund management achieved an effectiveness ratio of 100% in 2020, 2021, 2022, and 2024, and 100.89% in 2023, indicating effective to very effective performance throughout the study period. The primary strategy supporting this achievement was participatory bottom-up planning through village development deliberation forums. Conclusions: Effective village fund management in remote highland areas can be sustained through consistent budget realization supported by participatory governance mechanisms that strengthen transparency, accountability, and community involvement in decision-making. Limitations: The study is limited to a single village, covers only a five-year observation period, and relies mainly on budget realization ratios and a limited number of key informants. Contributions: This study contributes to the public governance literature by providing empirical evidence that participatory governance enhances fiscal accountability and supports effective village fund management in geographically isolated regions, offering practical insights for rural policymakers and village governments.